Mitosis is swell - Zatulovskiy, Evgeny (J Cell Biol, 2015)
Cell volume and dry mass are typically correlated. However, in this issue, Zlotek-Zlotkiewicz et al. (2015. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201505056) and Son et al. (2015. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201505058) use new live-cell techniques to show that entry to mitosis coincides with rapid cell swelling, which is reversed before division.